2009
DOI: 10.1039/b814082k
|View full text |Cite
|
Sign up to set email alerts
|

High-luminescence non-doped green OLEDs based on a 9,9-diarylfluorene-terminated 2,1,3-benzothiadiazole derivative

Abstract: We have prepared a highly efficient non-doped green organic light-emitting diode (OLED) incorporating a novel 9,9-diarylfluorene-terminated 2,1,3-benzothiadiazole green emitter (DFBTA), which exhibits an excellent solid state photoluminescence quantum yield (81%), and new triaryldiamines (DPAInT2, DPAInF) with high hole mobility derived from rigid and coplanar cores. The optimal device: ITO/DPAInT2/DPAInF/TCTA/DFBTA/Alq3/LiF/Al displayed impressive device characteristics, including a maximum external quantum e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 38 publications
0
21
1
Order By: Relevance
“…With 1 in hand, the next step was to introduce the bromine atoms on the dihydroindenofluorenyl core (step a. scheme 1), prior to the Pd-catalyzed cross-coupling reactions. Since the 2,7-positions of the fluorenyl moieties of 1 had been protected and as electrophilic bromination of dihydroindenofluorene derivatives had been previously reported in the literature, [54][55][56] we believed that the introduction of bromine atoms would be an easy task. However, it turns that the different reported conditions only led to very poor yields of 2 due to either over bromination reactions on the position C4 of the fluorene units or no bromination, highlighting the different reactivity of the spirofluorene-bridged dihydroindenofluorenyl unit compared to alkyl-bridged dihydroindenofluorenyl unit previously reported in the literature.…”
Section: Dd-dsf-ifmentioning
confidence: 99%
“…With 1 in hand, the next step was to introduce the bromine atoms on the dihydroindenofluorenyl core (step a. scheme 1), prior to the Pd-catalyzed cross-coupling reactions. Since the 2,7-positions of the fluorenyl moieties of 1 had been protected and as electrophilic bromination of dihydroindenofluorene derivatives had been previously reported in the literature, [54][55][56] we believed that the introduction of bromine atoms would be an easy task. However, it turns that the different reported conditions only led to very poor yields of 2 due to either over bromination reactions on the position C4 of the fluorene units or no bromination, highlighting the different reactivity of the spirofluorene-bridged dihydroindenofluorenyl unit compared to alkyl-bridged dihydroindenofluorenyl unit previously reported in the literature.…”
Section: Dd-dsf-ifmentioning
confidence: 99%
“…Phenylene-based oligomers and polymers are widely employed as optoelectronic materials in organic field effect transistors (OFETs), organic light-emitting diodes (OLEDs), and organic photovoltaics (OPVs). , Among them, dihydroindenofluorenes (DIFs; Figure ) and DIF-based polymers are particularly attractive for their ready accessibility, planarity of the π-framework associated with high optoelectronic performance, and structural diversity due to the direction of the fusion of the 6–5–6–­5–6 membered rings. As a result of different fusion modes, [1,2- a ]-, [1,2- b ]-, [2,1- a ]-, [2,1- b ]-, and [2,1- c ]-DIF isomers are known.…”
Section: Introductionmentioning
confidence: 99%
“…Subsitution of benzothiadiazole nucleus by electron-withdrawing substituents, such as fluorine and cyano has been demonstrated as a facile method for tuning the dipole moment and absorption of the dyes. Despite these efforts, the development of blue/green emitting materials with BTD motif is scarce. Besides, in recent years the investigation on structure–property relationship of regioisomers is highly demanding due to the significant changes in the physicochemical, thermal, and carrier transport properties by simple structural reorientation. For instance, Jiang et al reported nitrogen modified BTD core ([1,2,5]­thiadiazolo­[ 3,4- c ]­pyridine (PT)) substituted with triphenylamine and phenyl units on C4 and C7 positions which results in two asymmetric regioisomers, such as proximal p-TPA-PT ( N , N -diphenyl-4-(7-phenyl-[1,2,5]­thiadiazolo­[3,4- c ]­pyridin-4-yl) aniline) and distal d-TPA-PT ( N , N -diphenyl-4-(4-phenyl-[1,2,5]­thiadiazolo­[3,4- c ]­pyridin-7-yl)­aniline), dependent on the orientation of the nitrogen with respect to the donor triphenylamine.…”
Section: Introductionmentioning
confidence: 99%